Minimally Invasive Screw Fixation of Unstable Pelvic Fractures Using the "Blunt End" Kirschner Wire Technique Assisted by 3D Printed External Template. - Chen, Kaifang; Yao, Sheng; Yang, Fan; Drepaul, Deepak; Telemacque, Dionne; Zhu, Fengzhao; Zeng, Lian; Xiong, Zekang; Sun, Tingfang; Guo, Xiaodong (BioMed Research International, 2019)
Objective. This study aimed to determine the accuracy and safety of the "blunt end" Kirschner wire (KW) technique for the minimally invasive treatment of unstable pelvic fractures with the assistance of a 3D printed external template. Methods. Clinical data of 28 patients with unstable pelvic fractures between January 2016 and January 2018 were retrospectively analyzed. There were 6 cases of B1, 10 of B2, 8 of C1, and 4 of C2 fractures, all of which received surgical treatment. The "blunt end" KW technique with a 3D template was adopted for the minimally invasive placement of the iliosacral (IS) or superior ramus screws. The number of intraoperative fluoroscopies, surgical time, and complications were recorded. Postoperative reduction was assessed using the Matta criteria, and the Majeed score system was used to evaluate postoperative functional recovery. Results. The average number of fluoroscopies was 35 per patient, and the average surgical time was 85.2 min. A total of 19 S1 and 28 S2 IS screws were inserted. Eleven antegrade superior ramus screws and 4 retrograde screws were placed in 11 patients, and anterior subcutaneous internal fixation (INFIX) was used to fix the anterior pelvic ring in 17 patients. All patients were followed up for an average of 18 months. Postoperative reduction was evaluated by Matta's criteria: excellent in 16 cases, good in 9 cases, and fair in 3 cases. The Majeed score was used in the last follow-up to evaluate functional recovery: excellent in 13 cases, good in 10 cases, fair in 4 cases, and poor in 1 case. There were no cases of operative vascular injury. Conclusion. The "blunt end" KW technique with a 3D printed external template is a safe and effective method for the placement of IS and superior ramus screws in unstable pelvic fractures with minimized surgical duration and radiation exposure.